Discovery Of Peptoid Ligands For Anti-Aquaporin 4 Antibodies - Raveendra, Bindu (2013)
Neuromyelitis optica (NMO) is an autoimmune inflammatory disorder of the central nervous system. In most NMO patients, autoantibodies to the water channel protein Aquaporin 4 (AQP4) are present at high levels and are thought to drive pathology by mediating complement-dependent destruction of astrocytes. Here we apply recently developed chemical library screening technology to identify a synthetic peptoid that binds anti-AQP4 antibodies in the serum of NMO patients. This finding validates, in a well-defined human disease, that synthetic, unnatural ligands for the antigen-binding site of a disease-linked antibody can be isolated by high-throughput screening.